The motivation as a key factor in the development of the english productive skills with students of basic education at Gabriela Mistral No.1 school. Catamayo town. Academic year 2012-2013 - Moreno Torres, Rommel Alexander (2015)
The present research work entitled THE MOTIVATION AS A KEY FACTOR IN THE DEVELOPMENT OF THE ENGLISH PRODUCTIVE SKILLS WITH STUDENTS OF BASIC EDUCATION AT GABRIELA MISTRAL NO. 1 SCHOOL. CATAMAYO TOWN. ACADEMIC YEAR 2012-2013, had the purpose of knowing how motivation helps in the development of the English productive skills. Among the methods used in this research are: scientific, descriptive and analytical-synthetic; and the surveys applied teachers and students permitted to gather data that was used to know the function of motivation in the attainment of productive skills. The results show that teachers motivate students to develop the speaking skill, which is essential to produce oral speech; but, they do not motivate students to develop writing, which can lead to a bad written communication. Finally, it was determined that motivation has a decisive value in the development of the English productive skills in students of the researched Institution